Electrocaloric and pyroelectric properties of 0.6Basub(0.85)Casub(0.15)Zrsub(0.10)Tisub(0.90)Osub3–0.4BaTisub(0.89)Snsub(0.11)Osub3 ceramics - Merselmiz, Soukaina (Informacije MIDEM, 2024)
Ferroelectric materials are gaining considerable attention for energy storage, electrocaloric and pyroelectric energy harvesting applications. In particular, Ba0.85Ca0.15Zr0.10Ti0.90O3 (BCZT) and BaTi0.89Sn0.11O3 (BTSn) ceramics are among the best-studied lead-free BaTiO3-based ferroelectrics with high piezoelectric and electrocaloric properties. In this work, we prepared a 0.6BCZT–0.4BTSn solid solution. The structural, energy storage, electrocaloric, and pyroelectric properties are investigated. An energy density of 61.4 mJ cm-3 with a high energy efficiency of 82.4 % at 90 °C is achieved. The electrocaloric temperature change, which is determined indirectly via the Maxwell relation, is 0.5 K at 86 °C and 25 kV cm-1. It is stable over a wide temperature range of around 65 °C and has a coefficient of performance of 15. Moreover, a pyroelectric energy density of 124.1 mJ cm-3 is achieved. The results of this study show that the 0.6BCZT–0.4BTSn ceramics is a multifunctional material with energy storage, electrocaloric and pyroelectric properties.
Keywords: electrocaloric; electronic ceramics; elektrokalorik; elektronska keramika; energy harvesting; energy storage; keramika brez svinca; lead-free ceramics; piroelektrik; pyroelectric; shranjevanje energije; zbiranje energije